Effects of clopidogrel vs. prasugrel vs. ticagrelor on endothelial function, inflammatory parameters, and platelet function in patients with acute coronary syndrome undergoing coronary artery stenting: a randomized, blinded, parallel study. (3rd January 2020) - Schnorbus, Boris; Daiber, Andreas; Jurk, Kerstin; Warnke, Silke; Koenig, Jochem; Lackner, Karl J; Münzel, Thomas; Gori, Tommaso
Abstract: Aims: In a randomized, parallel, blinded study, we investigate the impact of clopidogrel, prasugrel, or ticagrelor on peripheral endothelial function in patients undergoing stenting for an acute coronary syndrome. Methods and results: The primary endpoint of the study was the change in endothelium-dependent flow-mediated dilation (FMD) following stenting. A total of 90 patients (age 62 ± 9 years, 81 males, 22 diabetics, 49 non-ST elevation myocardial infarctions) were enrolled. There were no significant differences among groups in any clinical parameter. Acutely before stenting, all three drugs improved FMD without differences between groups ( P = 0.73). Stenting blunted FMD in the clopidogrel and ticagrelor group (both P < 0.01), but not in the prasugrel group. During follow-up, prasugrel was superior to clopidogrel [mean difference 2.13, 95% confidence interval (CI) 0.68–3.58; P = 0.0047] and ticagrelor (mean difference 1.57, 95% CI 0.31–2.83; P = 0.0155), but this difference was limited to patients who received the study therapy 2 h before stenting. Ticagrelor was not significantly superior to clopidogrel (mean difference 0.55, 95% CI −0.73 to 1.82; P = 0.39). No significant differences were seen among groups for low-flow-mediated dilation. Plasma interleukin (IL)-6 ( P = 0.02 and P = 0.01, respectively) and platelet aggregation reactivity in response to adenosine diphosphate ( P = 0.002 and P = 0.035) were lower in the prasugrel compared to clopidogrel and ticagrelor group. Conclusion: As compared to ticagrelor and clopidogrel, therapy with prasugrel in patients undergoing stenting for an acute coronary syndrome is associated with improved endothelial function, stronger platelet inhibition, and reduced IL-6 levels, all of which may have prognostic implications. This effect was lost in patients who received the study medication immediately after stenting. EUDRACT-N o : 2011-005305-73